UNIFIED CORRELATION OF GEOMETRY CONSTRAINT WITH FRACTURE TOUGHNESS FOR THE INTERFACE CRACK IN BIMETALLIC JOINTS - YANG Jie; WANG GuoZhen; WANG YiHao (Jixie qiangdu)
A unified constraint characterization parameter Aphas been defined based on the homogeneous material A508 in the previous study of authors. However,it is not clear that whether the unified correlation of in-plane and out-of-plane constraint with fracture resistance can be established by using the constraint parameter for the dissimilar metal welded joints（ DMWJs） or the bimetallic joint with highly heterogeneous mechanical property（ material constraint）. In this paper,the J-resistance curves of specimens under different in-plane and out-of-plane constraints for bimetallic joint were obtained by the FEM simulations based on GTN（ Gurson-Tvergaard-Needleman） damage model. And the equivalent plastic strain distributions ahead of crack tips for specimens with different constraint were calculated by the FEM model. After the fracture toughness JICand Apunder different constraint conditions were obtained,the unified correlation of in-plane constraint and out-of-plane constraint with fracture toughness of bimetallic joint was investigated. The results show that the Apis an appropriate unified constraint parameter which can characterize both geometry and material constraint,and can be used to established the unified correlation line between the fracture toughness and geometry constraint in bimetallic joint.